A case of idiopathic middle cerebral artery occlusion and perforating branch aneurysm in an unusual location. Issue 1 (2022) - Maeda, Masatomo; Fukuda, Akihiro; Shinoda, Kouki; Tamura, Masakazu; Yamada, Masanobu; Nakagawa, Hidemitsu
No abstract available